2019
DOI: 10.3390/ijms20051146
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, DNA Damage, and Development of Obesity-Related Diseases

Abstract: Obesity has been recognized to increase the risk of such diseases as cardiovascular diseases, diabetes, and cancer. It indicates that obesity can impact genome stability. Oxidative stress and inflammation, commonly occurring in obesity, can induce DNA damage and inhibit DNA repair mechanisms. Accumulation of DNA damage can lead to an enhanced mutation rate and can alter gene expression resulting in disturbances in cell metabolism. Obesity-associated DNA damage can promote cancer growth by favoring cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(137 citation statements)
references
References 157 publications
5
124
1
7
Order By: Relevance
“…Cigarette smoke is a genotoxic agent inducing DNA damage [24]. In addition, also obesity induces DNA damage [25] and, furthermore, free fatty acids involved in obesity induce a release of mtDNA into the cytoplasm [15]. Together with our recent observation, we speculate that conditions such as smoking or obesity, resulting in an enhanced release of DNA, may fuel the process of aging in a STINGdependent manner by augmenting senescence, endothelial inflammation, and inflamm-aging ( Fig.…”
Section: Resultssupporting
confidence: 66%
“…Cigarette smoke is a genotoxic agent inducing DNA damage [24]. In addition, also obesity induces DNA damage [25] and, furthermore, free fatty acids involved in obesity induce a release of mtDNA into the cytoplasm [15]. Together with our recent observation, we speculate that conditions such as smoking or obesity, resulting in an enhanced release of DNA, may fuel the process of aging in a STINGdependent manner by augmenting senescence, endothelial inflammation, and inflamm-aging ( Fig.…”
Section: Resultssupporting
confidence: 66%
“…Obesity has been associated with low-grade sustained inflammation and oxidative stress, both classical triggers of cell cycle arrest [28]. In the present study, we demonstrated that maternal obesity increases the expression of several cell cycle regulators, i.e., 9 genes and 25 proteins, in the first trimester of pregnancy, suggesting that obesity affects placental cell cycle control already in early pregnancy.…”
Section: Discussionsupporting
confidence: 61%
“…The main factors associated with an increase in oxidative stress in menopausal women include obesity, aging, decreased estrogen production, and diet [4,[7][8][9]. Chronic inflammation is a hallmark of aging and obesity and has been implicated in the release of ROS from different sources, including activated macrophages and neutrophils involved in inflammation that generates oxidants, such as peroxynitrite and nitrosoperoxycarbonate, hypohalous acids, and nitrosating agent [7]. ROS can participate in lipid peroxidation and generate products such as etheno-, propano-, and malondialdehyde that interact with DNA, form DNA adducts, and damage the DNA structure [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation is a hallmark of aging and obesity and has been implicated in the release of ROS from different sources, including activated macrophages and neutrophils involved in inflammation that generates oxidants, such as peroxynitrite and nitrosoperoxycarbonate, hypohalous acids, and nitrosating agent [7]. ROS can participate in lipid peroxidation and generate products such as etheno-, propano-, and malondialdehyde that interact with DNA, form DNA adducts, and damage the DNA structure [4,7]. The protective effect of estrogen on oxidative stress is mediated by translocation for specific enzymes from the cytosol that prevent mitochondrial DNA from oxidative attack by free radicals [8].…”
Section: Introductionmentioning
confidence: 99%